Kriteria Keputusan Peningkatan Produktifitas Konfigurasi Ruang Di Rusunawa Dabag Kab. Sleman DI Yogyakarta - Ilham Fazri; Muhamad Rafif Naufal; Muhammad Rafli Alrizqi (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2024)
Low cost apartment complexes are often considered poorly maintained in enhancing space configuration productivity, so the apartment complex needs to have a space configuration that can enhance its productivity to meet operational building costs. The problem that often occurs in many low-cost apartment complexes is what decision criteria should be made to increase the productivity of space configuration, especially in the Dabag Yogyakarta apartment complex. This research uses the preferences and perceptions of residents interested in living in the low-cost apartment complex. Conduct validity testing at Dabag apartment complex with questionnaires and change the existing space configuration with a new configuration considering field conditions as an evaluation of supporting variables such as the proximity of the apartment complex and facilities and the investment costs that must be incurred. The result is that the Dabag apartment complex has criteria for making decisions to increase the productivity of higher space configurations by adding sports fields, playgrounds, gardens, and multipurpose rooms. The research results can be a reference in increasing the productivity of the space configuration of the needed flat complex.